Performance Evaluation of China's Basic Pension Insurance Based on a Three-Stage Superefficient SBM-DEA Model - Zexing Xue; Zhengping Ma (Discrete Dynamics in Nature and Society)
This study looks at the efficiency and effectiveness of the pension insurance system, thus establishing a pension insurance performance evaluation index system. Based on the SBM-DEA model with non-radial and non-angular outputs, the performance evaluation model of basic endowment insurance system was constructed using this index system. By studying the basic pension insurance for employees, this study analyses the basic pension insurance data of 31 provinces in China from 2016 to 2020 and conducts experiments. The results show that the overall performance of the basic endowment insurance system for urban workers in all provinces of China shows a downward trend. The development level of each province is obviously not balanced. The results also show clear regional characteristics and exhibit an east-high-high-low pattern with uncoordinated levels of development with each other. In view of this phenomenon, the Dagum is used to measure the spatial difference in the performance of the basic endowment insurance system. Finally, kernel is used to predict its dynamic evolution trend from the time dimension.